IN VITRO ANTIMCROBIAL ACTIVITY OF MANGIFERA INDICA L - Mohammed Ahmed, Salih Osman; Ahmed Omer, Mohammed Alfatih; Almagboul, Aisha Zoheir; Abdrabo, Ashraf Nabiel (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 2 (2005), 2005)
The chloroform, methanol and aqueous extracts    of Mangifera indica seeds  were     subjected to preliminary    antimicrobial  activity against   two Gram- positive bacteria   ( Bacillus subtilis, Staphylococcus aureus ) three Gram-negative bacteria Escherichia coli, Proteus vulgaris,  Pseudomonas aeruginosa  and two fungi, Aspergillus niger and Candida albicans. The seeds chloroform and methanol extracts showed high activity   against   all organisms tested. The aqueous   extract showed high activity against both Gram-positive    organisms   and    one   Gram-negative bacteria namely Proteus vulgaris , low     activity     against Escherichia coli,   and was   inactive against Pseudomonas aeruginosa.    Therefore the active chloroform and  methanol extracts were further tested against sixty clinical ; Staphyllococcus aureus (n=15 ), Escherichia coli (n=15 ), Proteus vulgaris  (n=15 ) and  Pseudomonas aeruginosa (n=15 ) and the aqueous extract was tested against thirty clinical isolates of Staphyllococcus aureus (n=15 ) and Proteus vulgaris  (n=15 ) collected randomly from  specimens from Sudanese patients.  The clinical isolates exhibited low susceptibility compared to the standard organisms. The standard organisms were tested against reference antibiotics (Ampicillin and Gentamicin). It was found that the chloroform extract of Mangifera indica seeds at 200 mg/ml was more effective than 20mg/ml Ampicillin and15ug/ml Gentamicin against the majority of the organisms tested.The methanol extract   at 200mg/ml was more effective than 40mg/ml Gentamicin against the organisms tested.The aqueous extract was more effective than 40mg/ml Ampicillin against the majority of the organisms tested. All  extracts were inactive against Aspergillus niger. Both chloroform and methanol extracts were active  against Candida albicans while the aqueous extract was inactive . Therefore C.albic ans is more susceptible than A.niger .The chloroform extract inhibited C.albicans with inhibitory action between 25-50mg/ml  Nystatin and the methanol extract inhibited C.albicans with inhibitory action almost similar to 10mg /ml Clotrimazole.Therefore the high activity of the plant might justify its uses in traditional medicine.